Discriminative power of Campylobacter phenotypic and genotypic typing methods - Duarte, Alexandra; Seliwiorstow, Tomasz; Miller, William G.; De Zutter, Lieven; Uyttendaele, Mieke; Dierick, Katelijne; Botteldoorn, Nadine (Journal of microbiological methods, 2016)
The aim of this study was to compare different typing methods, individually and combined, for use in the monitoring of Campylobacter in food. Campylobacter jejuni (n=94) and Campylobacter coli (n=52) isolated from different broiler meat carcasses were characterized using multilocus sequence typing (MLST), flagellin gene A restriction fragment length polymorphism typing (flaA-RFLP), antimicrobial resistance profiling (AMRp), the presence/absence of 5 putative virulence genes; and, exclusively for C. jejuni, the determination of lipooligosaccharide (LOS) class. Discriminatory power was calculated by the Simpson's index of diversity (SID) and the congruence was measured by the adjusted Rand index and adjusted Wallace coefficient. MLST was individually the most discriminative typing method for both C. jejuni (SID=0.981) and C. coli (SID=0.957). The most discriminative combination with a SID of 0.992 for both C. jejuni and C. coli was obtained by combining MLST with flaA-RFLP. The combination of MLST with flaA-RFLP is an easy and feasible typing method for short-term monitoring of Campylobacter in broiler meat carcass. •MLST/flaA-RFLP combination had the highest typing discrimination in this study.•Discriminatory power of combined methods relies on congruence between methods.•MLST/flaA-RFLP is feasible for short-term monitoring of broiler meat for Campylobacter.•MLST/flaA-RFLP and MLST/AMRp provided equivalent discriminatory power.